WORK MOTIVATION OF TEACHERS IN THE SCHOOL UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE, NONTHABURI - Jongjitsuk, Sukanya; Phophet, Vinutthaput (Journal of Educational Review Faculty of Education in MCU, 2025)
The objectives of the research were 1) to study work motivation of the teachers, and 2) to compare the opinions of the teachers on work motivation of teachers in the school under the Secondary Educational Service Area Office, Nonthaburi, classified by gender, age, academic status, education level and work experience. The sample consisted of 404 teachers selected through stratified random sampling according to school size. The research instrument was a questionnaire with content validity, IOC values between .67-1.00, a reliability value of .98. The data were analyzed by using frequency, percentage, mean, standard deviation, t-test, One-way ANOVA, and LSD. The study found that: 1) the work motivation of teachers overall, motivator factors and hygiene factors were at a high level, regarding in the motivator factors, the aspect of Achievement was the highest average, rated at the highest level, followed by Responsibility, Advancement and Growth, Work Itself, and Recognition, respectively, all were at a high level. For the hygiene factors, both the overall and each aspect were at a high level. The highest average was found in Occupational status, followed by Personal life, Policy and Administration, Supervision Technical, Job security, Interpersonal relationships, Salary, and Work conditions, respectively. 2) The comparison of work motivation of the teachers, classified by gender and age, there were no statistically significant differences in overall, the motivator factors, and the hygiene factors. However, when classified by educational level and academic status, significant differences were found in overall and the motivator factors, which showed a statistically significant difference at the .01 level, and the hygiene factors showed a statistically significant difference at the .05 level. When classified by work experience, in overall, the motivator factors, and the hygiene factors showed statistically significant differences at the .01 level.